The Effect of Strassburg Sock Orthosis on Heel Pain and Quality of Life in Patient with Plantar Fasciitis Lesion - Tahmores Tahmasbi; Saideh Mohammadi (Vesnu Publications, 2020)
Introduction: Plantar fasciitis is the most common reason for heel pain and the result of some repetitive trauma in calcaneus. People with plantar fasciitis need to be treated through some stretching techniques for plantar fascia and calf muscles, and some anti-inflammatory treatments. Materials and Methods: In this randomized clinical trial study, 28 patients with plantar fasciitis were selected through convenience sampling method. Individuals with morning pain and tenderness in the insertion of plantar fascia were included, and were assigned in two control and experimental groups. Individuals with a history of surgery, dislocation, and fracture in the lower limb were excluded. Then, they were referred to technical orthopedic clinics for night splinting. The heel pain and quality of life were assessed through Visual Analogue Scale (VAS) and Foot Ankle Outcome Questionnaire, respectively, before treatment, and at the end of the first, fourth, and sixth weeks. The collected data were compared between the groups using independent t test with a significant level of P < 0.05. Results: Regarding pain, daily activity, and sport, there were significant differences between the control and experimental groups at the fourth and sixth weeks. In terms of foot and ankle problems and quality of life, there were significant differences between the control and experimental groups at the first, fourth, and sixth week Conclusion: The current study indicates that prefabricate orthotic may be effective in pain relief of the heel, improvement of daily activities, and doing sport over time. Ultimately, the use of this splint increases the quality of life and decreases foot and ankle problems in the people with plantar fasciitis.